Electric Stimulation of Ammonotrophic Methanogenesis - Siegert, Michael; Tan, Allen (Frontiers in Energy Research, 2019)
Reduced nitrogen compounds like ammonium or amines are ubiquitous constituents of wastewater. As source of electrons, they can be oxidized without producing CO2. This makes them ideal for biogas upgrading in microbial power-to-gas processes in wastewater treatment plants as well as for energy storage. Here, we tested the hypothesis whether ammonium or total nitrogen can be oxidized to N2 while producing energy-rich chemicals such as H2 or methane. First, we show that ammonium oxidation can be coupled to H2 production in microbial electrolysis cells. We show that with ammonium and water as the only sources of electrons, N2 gas was produced at potentials of +550 and +400 mV vs a standard hydrogen electrode. Since H2 can neither be stored, nor transported without major upgrades of our infrastructure, we further tested the hypothesis whether wastewater nitrogen can be oxidized and used to produce methane. At a potential of +500 mV, N2 was produced from domestic wastewater while total nitrogen was removed. We compared two different types of anodes, graphite granule drums and carbon brushes, and found that both were comparable in terms of performance. The drums were slightly better in removing chemical oxygen demand, whereas the brushes produced methane faster. Our research shows that nitrogen contained in wastewater can replace water oxidation in electrolytic biogas upgrading.